The Binding of HSPA8 and Mitochondrial ALDH2 Mediates Oxygen-Glucose Deprivation-Induced Fibroblast Senescence - Wenting Hui; Tongtong Song; Ling Yu; Xia Chen (MDPI AG, 2023)
Cellular senescence refers to the permanent and irreversible cessation of the cell cycle. Recently, it has gained significant interest as a promising target for preventing cardiovascular diseases. Aldehyde dehydrogenase 2 (ALDH2) is a mitochondrial enzyme that has been closely linked with an increased risk of cardiovascular diseases. In this study, bioinformatics analysis revealed that the signaling pathway for fibroblast senescence is significantly activated in mice after myocardial infarction (MI), and that ALDH2 might be a crucial molecule responsible for inducing this change. Therefore, we created an NIH3T3 fibroblast cell line oxygen-glucose deprivation (OGD) model to replicate the conditions of MI in vitro. We further revealed that decreased ALDH2 enzyme activity is a critical factor that affects fibroblast senescence after OGD, and the activation of ALDH2 can improve the mitochondrial damage caused by OGD. We identified Heat Shock 70-kDa Protein 8 (HSPA8) as an interacting protein of ALDH2 through co-immunoprecipitation (Co-IP) and mass spectrometry (MS) detection. Subsequently, our studies showed that HSPA8 translocates to the mitochondria after OGD, potentially binding to ALDH2 and inhibiting its enzyme activity. By transfecting siRNA to inhibit HSPA8 expression in cells, it was found that ALDH2 enzyme activity can be significantly increased, and the senescence characteristics induced by OGD in NIH3T3 cells can be improved. In conclusion, the data from this study suggest that HSPA8, in conjunction with ALDH2, could regulate fibroblast senescence after oxygen-glucose deprivation, providing a new direction and foundation for effectively intervening in fibroblast senescence after myocardial infarction.